US-India Relations in the Indo-Pacific Under the Joe Biden Administration - Muhammad Taimoor; Dr. Ghulam Mustafa; Muhammad Rehan Akram; Muhammad Waqas Anwar (Dialogue Social Science Review (DSSR), 2025)
Under President Joe Biden's administration, U.S.-India relations have deepened significantly, reflecting a shared commitment to stability in the Indo-Pacific region, defense collaboration, economic growth, and addressing global challenges. Rooted in strategic alignment, the bilateral relationship has been bolstered by initiatives like the Quadrilateral Security Dialogue (Quad) and 2+2 Ministerial Dialogues, focusing on countering China's regional assertiveness. Defense agreements, such as BECA, and joint military exercises, notably the Malabar Exercise, have enhanced India's capabilities and cemented the U.S. as a vital partner in South Asia's security architecture. Economically, the two nations have strived to resolve trade barriers, promote investments, and foster technological collaborations, particularly in sectors like artificial intelligence and semiconductor manufacturing. Beyond security and economics, the U.S. and India have collaborated on global challenges, including climate change and the COVID-19 pandemic, demonstrating a commitment to multilateralism. Through the U.S.-India Climate and Clean Energy Agenda 2030, both countries aim to lead in sustainable energy practices. Additionally, their joint efforts in vaccine distribution highlight their humanitarian and strategic partnership. While challenges persist in trade and policy alignment, the Biden administration's focus on India underscores the bilateral relationship's pivotal role in promoting a rules-based international order. This article examines the multifaceted dimensions of U.S.-India relations, highlighting their evolution and prospects in a complex geopolitical environment.